Analog layout synthesis a survey of topological approaches - Graeb, Helmut E.; SpringerLink (Online service). (New York Springer, 2011)
Analog Layout Synthesis: A Survey of Topological Approaches Edited by: Helmut E. Graeb Analog components appear on 75% of all chips, and cause 40% of the design effort and 50% of the re-designs. Due to increasing functional complexity of systems-on-chip, the difficulties in analog design and the lack of design automation support for analog circuits make analog components a bottleneck in chip design. Design methodology and design automation for analog circuits therefore is a crucial problem for developing systems-on-chip and layout synthesis is a key part of the analog design flow. Layout design is the step of the analog design flow with the least support by commercially available, computer-aided design tools. This book provides a survey of promising new approaches to automated, analog layout design, which have been described recently and are rapidly being adopted in industry. Presents a comprehensive survey of promising new methods for automated, analog layout design; Covers a variety recent of approaches to topological placement of analog circuits; Provides a comprehensive overview of routing issues and techniques for analog circuits; Provides a complete view of analog layout in the design flow, including retargeting an existing layout for a new technology, integrating layout in the sizing process, and constraint management; Represents a one-of-a-kind, single-source reference to the latest advances in analog layout synthesis.
Device-level topological placement with symmetry constraints -- Hierarchical placement with layout constraints -- Enhanced shape functions for deterministic analog placement -- Free-Shape Routing for Analog and RF circuits -- Closing the gap between electrical and physical design of analog circuits: the layout-aware solution -- Analog layout retargeting -- Template-driven analog layout automation -- Place and route of analog circuits.
Electronic reproduction.
Keywords: Integrated circuit layout; Linear integrated circuits -- Design; Electronic books